Tribes and The State in The Post-Armed Areas of Ramadi And Fallujah: Socio-Anthropological Study - Mohammed, Muayad Manfi (International Journal of Psychosocial Rehabilitation, 2020)
The study deals with the topic of the participation of tribesmen in the state institutions in the societies of Ramadi - and Fallujah at the present time. The aim of the research is to reveal the clan’s political role and understanding the political role of the state in the present time, and its impact on the Anbarian community, represented by Ramadi and Fallujah in the post-armed conflict stage. Shedding the light on the representation of the parliamentarians of the tribesmen. The research also depends on the socio-anthropological methodology expected, which is not specific, and the research relied on the means of information collecting. The most prominent of which were: Observing with participation, interview, records, and informants. As for the expected sample, it is an intention sample of (100) individuals to obtain basic information and data that cannot be obtained by other means. As for the expected results of the research, the tribal community in Anbar has a role in filling positions for the state. There is an agreement among the various clans that, it is the basis on which the local government in the province is built for the clans, and it has an important role in charting the future of the province in a distinct manner and these are the leaders of the provincial councils and parliament. Finally, one of the expected results is that the tribe today has a role in changing political alliances on the Iraqi scene, especially in Anbar Governorate during the elections.